No evidence for the inverted U-Curve: More demanding dual tasks cause stronger aversive memory degradation. (December 2019) - Littel, Marianne; van Schie, Kevin
Abstract: Background and objectives: Simultaneously making eye movements and recalling a memory leads to competition in working memory (WM), which reduces memory vividness and emotionality. The dose-response relationship between WM taxation and aversive memory degradation is predicted to be either linear (i.e., more cognitively demanding tasks exhibit stronger effects) or follow an inverted U-curve (i.e., there should not be too little, but also not too much taxation). Methods: Participants ( N  = 44) recalled four aversive autobiographical memories under four conditions that differed in WM taxation: complex, intermediate, simple, or no counting. Before and after each intervention, and at 24 h follow-up, participants recalled the aversive memory and rated it on vividness and unpleasantness. Using a Bayesian approach the linear and inverted U-shape relationships were directly compared. Results: Pretest to posttest drops in vividness and unpleasantness became larger with increased WM taxation of the counting conditions. There was no support for either hypotheses from pretest to follow-up for memory unpleasantness, whereas for memory vividness anecdotal evidence was found for a linear relationship. Limitations: A reaction time (RT) task was used to select counting tasks of varying difficulties. However, the validity of this task appears to be compromised under very strenuous conditions. Higher levels of WM taxation might have been possible with more difficult counting tasks. Conclusions: There is strong evidence for a linear dose-response relationship between WM taxation and memory degradation immediately after the intervention, and some unconvincing evidence for this pattern one day later. There was no evidence for an inverted U-curve. Highlights: There is a linear relationship between memory taxation and memory degradation. One day later there is some, yet unconvincing, evidence for this linear pattern. No inverted U-curve relationship was observed between taxation and degradation.